MANAJEMEN KONFLIK DALAM SUPERVISI PENDIDIKAN - ahmad, Fadli; Ahmad Manshur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine conflict management in educational supervision through a qualitative approach using the library research method. Conflict in educational supervision is an inevitable phenomenon arising from differences in interests, competencies, values, and authoritative positions between supervisors and teachers. This study identifies five common conflict typologies in the supervisory context, namely interpersonal, structural, value, interest, and role conflict. The causative factors are grouped into two dimensions: internal factors including ineffective communication, competency differences, and procedural ambiguity, and external factors such as policy pressures, resource limitations, and unconducive group dynamics. The findings indicate that the collaborating model is the most effective approach in managing supervisory conflicts, whose implementation should be integrated within a humanistic supervision paradigm based on dialogic communication, institutional mediation, supervisor capacity development, and sustainable preventive conflict management mechanisms in order to realize high-quality and dignified educational supervision.